PENERAPAN STRATEGI PEMBELAJARAN TIPE INDEX CARD MATCH TERHADAP KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS V DI SDN DURI KOSAMBI 07 PAGI - Aliftra Rima Rachmadani; Nana Hendracipta; Reksa Adya Pribadi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
Numerical literacy skills are very much needed in learning mathematics, because mathematics is not only always related to formulas, but also requires reasoning or critical thinking patterns from students in answering every problem presented. The use of various learning strategies can make it easier for students to understand numeracy literacy, and create an active learning atmosphere for students to produce better students' numeracy literacy skills. This study aims to determine differences in students' numeracy literacy abilities through the use of index card match type learning strategies and make a match learning strategies. This study used a quasi-experimental method, with a non-equivalent control group design. The population in this study were all fifth grade students at SDN Duri Kosambi 07 Pagi. Sampling in this study used purposive sampling, the VA class became the experimental class and the VD class became the control class. The results of this study show that the average score of the VA class students who used the index card match type learning strategy was 74.47 while the average score of the VD class students who used the make a match learning strategy was 58.63. That way, it can be concluded that there are differences in the numeracy literacy abilities of students who use the index card match type learning strategy and students who use the make a match learning strategy. In addition, the numeracy literacy skills of students who use the index card match type learning strategy are better than students who use the make a match learning strategy.